Integration chatter avoidance and minimum quantity lubrication condition in machining process - Wan Mohd Azlan, Wan Mohd Nowalid (2019)
Machining processes with high productivity cause tool wear and materials defects even damage machine spindle and limited by self-excited vibration or chatter. Cutting operations represent the largest process of manufacturing activities in machining process. At the same time, it produces different cutting force value depends on method of cutting, geometry of the tools and speed variation. This high material removal rate can be also achieved at high speed conditions, however, it consumes very high cutting fluid utilization. The main objective of this project is to compensate between chatter avoidance as high quality of product and productivity, while minimal quantity lubrication (MQL) deals with low cost of productivity and environmental effect in machining processes. In order to achieve this objective, cutting force stiffness under dry, flood and minimal quantity lubrication with speed dependence is determined. This chatter vibration in cutting processes can suppress by using chatter stability prediction, particularly at lobbing effect where stable cutting locating at certain speed. To validate the chatter stability of various types cutting fluid conditions experimentally, stable or unstable (chatter) cutting within range of specific speed and depth of cut were checked. Finally, to apply the concept combine between the chatter avoidance and MQL, machining process was employed in machining process of thin walled structure. The experiments were designed to evaluate the performance of the method used at various spindle speed of 1500, 3000, 4500, 6000 and 7500 rev/min and feed rates of 0.025, 0.05, 0.075, 0.010 and 0.125 mm/tooth. Results showed that a slight different cutting coefficients that obtain from milling force from x and y direction using Dynamometer 9275b at different cutting speeds obtained from lubrication of dry, flood and MQL experiment compare with mechanics of cutting models. Finally, the thin wall structures shape applied the integration of MQL and chatter avoindance in stability lobe for increasing the machining depth of cut. In conclusion, with the changing lubrication conditions, the values of cutting force coefficients identified differ for different lubrication conditions despite on milling force measured by dynamometer in x and y direction. Therefore, the integration of chatter avoidance and minimal quantity lubrication can be applied and achieved the sustainable manufacturing process with high productivity, low machining cost and precision product.